Homo Homini Amicus: Tanggungjawab Kultural Gereja Dalam Zaman Ini - Raymundus I Made Sudhiarsa (Seri Filsafat Teologi, 2020)
This article is to promote the values of friendship from the Christianity anthropology perspective in the frame of nation community as a shared-home. Very often, friendship is reduced exclusively on ‘in-group’ and enriched by primordial mentality (religion, culture, race, communities in the society). They who don’t agree with the values lived by the ‘in-group’ regarded as ‘the others’, even, treated as dangerous opponents. Firstly, to build a great cultured society, the concept of ‘friendship’ (Latin: amicitia; Greek: philia) should be re-defined. In the Christianity anthropology, friendship, as the highest form of relationship, has its source in the belief that man is created in ‘God’s image’ (Gen 1:26-28), who has the responsibility to manage the shared-world to live together in harmony. Secondly, the Catholic education institutions, from elementary to university, need to continually self-empowered with the spirituality of friendship which promotes more civilized humanity, ‘with all your heart, and with all your soul, and with all your mind, and with all your strength’ (Mark 12:30)